Icariin Induces Osteoblast Differentiation and Mineralization without Dexamethasone in Vitro - Ma, Xiao-Ni; Zhou, Jian; Ge, Bao-Feng; Zhen, Ping; Ma, Hui-Ping; Shi, Wen-Gui; Cheng, Kui; Xian, Cory J.; Chen, Ke-Ming (Planta Medica, 2013)
An effective method for preventing bone loss is by promoting osteoblast differentiation and bone formation. While dexamethasone has been routinely used as a classical inducer for osteoblast differentiation, limitations have been observed with its usage, including its varied effects on expression of osteoblast genes in different species and its potentials in suppressing osteoblastic differentiation and mineralization. In this study, we assessed the ability of flavonoid icariin in enhancing differentiation and mineralization of cultured rat primary osteoblasts in the absence of dexamethasone. It was found that, compared to the non-stimulated control, icariin at 10−5 M produced a higher alkaline phosphatase activity, more and larger areas of alkaline phosphatase-positive colonies (CFU-FALP) and mineralized nodules, more osteocalcin secretion and calcium deposition, higher levels of mRNA expression of alkaline phosphatase, osteoblastic transcription factors osterix and runt-related transcription factor 2, and collagen 1α, higher levels of protein expression of collagen 1α, alkaline phosphatese, osterix, and runt-related transcription factor 2. In addition, icariin at 10−5 M was always more potent than dexamethasone at its optimal concentration of 10−8 M on the above osteoblast differentiation and mineralization markers. Taken together, our studies demonstrated that icariin has a pronounced ability in promoting osteoblast differentiation in vitro in the absence of dexamethasone.
Keywords: osteoblasts; differentiation; icariin; proliferation; dexamethasone